Detection of single nucleotide polymorphisms (SNPs) in a SARS-CoV-2 virus strain in Vietnam - Thach, Tran Xuan; Duong, Bui Thi Thuy; Truong, Le Van; Hoa, Nguyen Thi; Lanh, Pham Thi; Uy, Nguyen Thai; Mai, Le Quynh; Anh, Dang Duc; Khang, Dinh Duy; Quyen, Dong Van (Academia Journal of Biology, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of a pandemic of acute respiratory disease in humans. This pandemic has now spread worldwide and caused more than 2,000,000 deaths by 15 January 2021. The complexity and the ongoing pandemic of coronavirus SARS-CoV-2 make it difficult to control the disease. Sequence analysis on some open reading frames (ORFs) of a SARS-CoV-2 virus strain isolated in Vietnam in February 2020 (SARS-CoV-2/NIHE/human/2020/VIE strain) revealed some single nucleotide polymorphisms (SNPs) that only appeared in the Vietnamese strain in comparison to those of the isolates in other countries, including: (1) a change in ORF8-Nucleocapsid (accession number MT127114.1) at nucleotide (nt) 691 (CTC in SARS-CoV-2/NIHE/human/2020/VIE strain, TTC in all other isolates) but it does not change the encoded amino acid, (2) ORF3a-EM-ORF6-ORF7a region (accession number MT127115.1) has four-point changes, three of which lead to changes in the amino acid sequences, being nt 479 (GTA encoding Valine changed into TTA encoding Leucine), nt 575 (CGC encoding Arginine changed to GGC encoding Glycine) in the M gene, and nt 1126 (GTG encoding Valine changed to GAG encoding Glutamic acid) in ORF6. Taken together, the results provided useful information for the SARS-CoV-2 diagnostic kit and vaccine development.